Feasibility study on the effectiveness of Goreisan‐based Kampo therapy for lower abdominal lymphedema after retroperitoneal lymphadenectomy via extraperitoneal approach. Issue 9 (25th May 2015) - Komiyama, Shinichi; Takeya, Chiaki; Takahashi, Rena; Yamamoto, Yasuhiro; Kubushiro, Kaneyuki
Abstract Aim To evaluate the efficacy and safety of Kampo therapy based on Goreisan for lower abdominal lymphedema after surgical treatment of endometrial cancer or cervical cancer. Methods Radical surgery, including retroperitoneal lymphadenectomy, was performed for endometrial cancer and cervical cancer. After surgery, Kampo therapy based on Goreisan and integrated physical therapy were provided for patients with lower abdominal lymphedema, especially lymphedema affecting the pubic‐inguinal‐vulval region. Goreisan (7.5g/day) was given orally three times a day (tds). If a significant response was not observed, Saireito (9 g/day; 3 g tds) or Gosyajinkigan (7.5 g/day; 2.5 g tds) was administered concomitantly. Results A total of 21 patients received treatment. The response rate to Goreisan monotherapy was 78%, with 22% being non‐responders. Median reduction of abdominal circumference was 2.1cm (95% CI 1.3‐2.85). When Goreisan was combined with another Kampo agent, the response rate was 92% and the non‐response rate was 8%. The median reduction of the abdominal circumference was 2.85 cm (95% CI: 2.25‐3.3). In particular, concomitant Goreisan and Saireito therapy achieved satisfactory results. No severe adverse reactions occurred. Conclusions Goreisan‐based Kampo therapy might be effective and safe for lower abdominal lymphedema after retroperitoneal lymphadenectomy. We will perform a prospective control study in the near future.